Home Literacy Environment: The Solution to Improve Early Reading Skills of Students in Primary School During COVID-19 - Nuryanti, Nuryanti; Iswara, Prana Dwija (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This research is motivated by the lack of research analyzed the early reading skills of students in a primary school in term of literacy activities at home. The literature indicates that both in-school and at-home experiences impact children’s reading development, yet most developing world studies focus on children’s in-school experiences exclusively. Whereas in the era of the Covid-19 pandemic literacy activities at home have an important role. In this article, we review the literature on the impact of home literacy environment on primary school student’s early reading skills. After defining the home literacy environment, we present a brief historical overview of the home literacy environment, including persistent questions regarding their effectiveness for early literacy skills, vocabulary, and phonological awareness in primary school students. Meta-analyses reveal that the home literacy environment has a positive effect on early reading skills indicate that they are effective in significantly increasing children’s early literacy skills, vocabulary, and phonological awareness. This finding lends empirical support for the home literacy environment and reading acquisition. We conclude by suggesting implications for practice and future research.